Maxims in Old English poetry - Cavill, Paul (1996)
The focus of the thesis is on maxims and gnomes in Old English poetry, but the occasional occurrence of these forms of expression in Old English prose and in other Old Germanic literature is also given attention, particularly in the earlier chapters.